An assessment of the moral permissibility of medical assistance in death through an act-utilitarian perspective - Yow, Rachael (Nanyang Technological University, 2023)
In recent years, the practice of euthanasia and physician-assisted suicide has become more widely accepted as a viable course of action in the face of the unbearable pain from a terminal illness. While some countries have already begun to legalise the practice of Medical Assistance in Dying (MAiD) under regulatory frameworks, this topic remains highly controversial and is heavily debated in terms of its impact on widespread legalisation. In this paper, I delve into the moral aspect of MAiD instead and examine it through the lens of one of the most fundamental theories of morality, act-utilitarianism. I argue not for the legalisation of MAiD, but the moral permissibility of committing this act that has been discussed in the same breath as terms like “murder” and “disrespect for life”. On the basis that a patient expresses a desire for MAiD and this desire is due to a prolonged period of suffering, an act-utilitarian approach towards the evaluation of its moral permissibility would find that going through with MAiD brings about the highest sum total of positive utility, rendering it morally permissible. With my contribution to the discussion regarding the moral status that we should assign to MAiD, I hope to play a part, no matter how small, in reducing the social stigma surrounding the decision to choose death in the face of otherwise unbearable circumstances in life.